Mourning in the View of Sigmund Freud and Melanie Klein (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
This article examines the concept of mourning from the psychoanalytic perspectives of Sigmund Freud and Melanie Klein, aiming to compare similarities and differences between their theories. Freud defines mourning as a natural withdrawal of libido from the lost object, distinguishing it from melancholy. Klein, however, views mourning as a reactivation of the infantile depressive position, involving guilt and reparation. Despite structural differences, both theorists regard mourning as a fundamental and universal process of psychic reconstruction following loss.
Keywords: Mourning; Melancholy; Loss; Freud; Klein